Current Interventional and Surgical Management of Congenital Heart Disease: Specific Focus on Valvular Disease and Cardiac Arrhythmias. Issue 6 (17th March 2017) - Holst, Kimberly A.; Said, Sameh M.; Nelson, Timothy J.; Cannon, Bryan C.; Dearani, Joseph A.
Abstract : Successful outcome in the care of patients with congenital heart disease depends on a comprehensive multidisciplinary team. Surgery is offered for almost every heart defect, despite complexity. Early mortality for cardiac surgery in the neonatal period is ≈10% and beyond infancy is <5%, with 90% to 95% of patients surviving with a good quality of life into the adult years. Advances in imaging have facilitated accurate diagnosis and planning of interventions and surgical procedures. Similarly, advances in the perioperative medical management of patients, particularly with intensive care, has also contributed to improving outcomes. Arrhythmias and heart failure are the most common late complications for the majority of defects, and reoperation for valvar problems is common. Lifelong surveillance for monitoring of recurrent or residual structural heart defects, as well as periodic assessment of cardiac function and arrhythmia monitoring, is essential for all patients. The field of congenital heart surgery is poised to incorporate new innovations such as bioengineered cells and scaffolds that will iteratively move toward bioengineered patches, conduits, valves, and even whole organs.